Utilizing the apical-out enteroids in vitro model to investigate intestinal glucose transport, barrier function, oxidative stress, and inflammatory responses in broiler chickens - Mann, Peter; Liu, Jundi; Yu, Liang-en; Wolfenden, Ross; Li, Yihang (Frontiers in Physiology, 2024)
Introduction Conventional 2D intestinal epithelial cell lines have been widely used in investigating intestinal functions, yet with limitations in recapitulating the in vivo gut physiology of chickens. A recently established chicken enteroid model with apical-out nature and the presence of leukocyte components represents intestinal mucosal functions. The objectives of this study were to 1) evaluate basic gut nutrient transport and barrier functions in this model and 2) identify the model’s effectiveness in studying inflammation and oxidative stress responses. Methods Enteroids were generated from individual villus units isolated from the small intestine of Cobb500 broiler embryos. Enteroid viability, morphology, and epithelial cell markers were monitored; barrier function was evaluated based on the permeability to fluorescein isothiocyanate–dextran (FD4) with or without EDTA and lipopolysaccharide (LPS) challenges; nutrient transport was evaluated by fluorescence-labeled glucose (2NBD-G) with or without transporter blockade; the oxidative status was indicated by reactive oxygen species (ROS). Inflammatory and oxidative challenges were induced by LPS and menadione treatment, respectively. Selected marker gene expressions, including tight junction proteins (CLDN-1, CLDN-2, ZO-1, and OCCL), epithelial cell markers (Lgr-5, LYZ, and MUC-2), cytokines (IL-1β, IL-6, IL-8, IL-10, TNF-α, and INF-γ), and antioxidant enzymes (Nrf-2, catalase, and SOD), were determined by using RT-qPCR. Data were analyzed by one-way ANOVA among treatment groups. Results Enteroid cell activity was stable from day (d) 2 to d 6 and declined at d 7. Epithelial cell marker and cytokine expressions were stable from d 4 to d 6. FD4 permeability was increased after the EDTA treatment (P ≤ 0.05). Transporter-mediated 2NBD-G absorption was observed, which was reduced with glucose transporter blockade (P ≤ 0.05). Enteroids showed classic responses to LPS challenges, including upregulated gene expressions of IL-1β and IL-6, downregulated gene expressions of ZO-1 and OCCL, and increased FD4 permeability (P ≤ 0.05). Enteroids showed increased ROS generation (P ≤ 0.05) in response to oxidative stress. Discussion In conclusion, this apical-out enteroid model is a stable alternative in vitro model that exhibits intestinal barrier, nutrient transport, oxidation, and inflammation functions. With this enteroid model, we developed two challenge protocols for evaluating intestinal functions under oxidative stress and inflammation conditions.